Preparation method of poly (ethylene 2, 5-furandicarboxylate)

Through multi-step purification and the use of high selectivity catalysts, the problem of dark color of polyethylene 2,5-furandiformate products was solved, and higher purity and better color performance were achieved.

CN119463141AActive Publication Date: 2025-02-18SHANDONG IND RES ZHONGKE HIGH END CHEM IND TECH RES INST CO LTD

Patent Information

Application Number
CN202510051666.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing polyethylene 2,5-furandiformate (PEF) products have darker colors, mainly because of the insufficient purity of FDCA and the improper selection of catalysts, resulting in side reactions and abnormal color.

Method used

Multi-step purification of 2,5-furandicarboxylic acid using activated carbon, dealdehyde resin and modified adsorbent to reduce impurity content; use a mixture of aluminum acetylacetonate, antimony triphenyl diacetate and zinc acetate as catalyst to reduce side reactions and the use of composite stabilizer inhibits oxidation reaction and improves the color of PEF.

Benefits of technology

It effectively reduces the content of acyl furoic acid, furoic acid and aldehyde impurities, reduces the color of the finished product, improves the color and stability of PEF, and avoids the occurrence of side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of bio-based polyester synthesis, in particular to a preparation method of poly (ethylene 2, 5-furandicarboxylate). Comprising the following steps: purification of 2, 5-furandicarboxylic acid: purifying the 2, 5-furandicarboxylic acid by sequentially adopting activated carbon, dealdehyding resin and a modified adsorbent, so that the content of acyl furoic acid, furoic acid and aldehyde impurities can be effectively reduced, side reactions are reduced, and the chroma of a finished product is reduced. Adding the purified 2, 5-furandicarboxylic acid, ethylene glycol, a composite catalyst and a composite stabilizer into a reaction container, and carrying out esterification reaction and polycondensation reaction to obtain 2, 5-furandicarboxylic acid glycol ester; a mixture of aluminum acetylacetonate, antimony triphenyl diacetate and zinc acetate is used as a catalyst of poly (ethylene 2, 5-furandicarboxylate), so that the color of PEF can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bio-based polyester synthesis, and in particular to a method for preparing polyethylene 2,5-furandicarboxylate. Background Art

[0002] Poly(ethylene 2,5-furandicarboxylate) (PEF), as a new bio-based polyester material, has excellent gas barrier properties, biocompatibility and mechanical properties, and is considered an ideal substitute for petroleum-based polyester. However, in the actual synthesis process, PEF products prepared using 2,5-furandicarboxylic acid (FDCA) and ethylene glycol (EG) as raw materials are often dark in color, which greatly limits its application range.

[0003] Analyzing the reasons, the lack of purity of FDCA is a key factor. In the preparation process of FDCA, a variety of impurities may be introduced, such as formyl furoic acid (FFCA), furoic acid (FCA) and other aldehyde impurities. The presence of these impurities will not only affect the purity of FDCA, but also trigger a series of side reactions in the subsequent esterification and polycondensation reactions, causing the color of the PEF product to darken. In particular, aldehyde impurities are very likely to trigger oxidation and polymerization reactions to generate colored byproducts, which seriously affect the color of PEF.

[0004] In addition, the selection and use of catalysts are also important reasons for the darkening of PEF color. In the synthesis process of PEF, commonly used catalysts include titanium, tin and antimony. However, these catalysts may induce some side reactions during the reaction, such as decarboxylation and etherification, which will generate colored by-products, causing the color of PEF to deepen. At the same time, some catalysts such as manganese and cobalt catalysts may also cause abnormal color of PEF. In addition, the toxicity of the catalyst cannot be ignored. Some commonly used catalysts such as tin catalysts may cause harm to the human body and the environment, which to a certain extent limits the widespread application of PEF.

[0005] In summary, insufficient purity of FDCA and improper selection and use of catalysts are the main reasons for the dark color of PEF. In order to prepare PEF products with light color and excellent performance, it is necessary to further optimize the purification process of FDCA and reduce the impurity content; at the same time, it is also necessary to screen out highly selective and low-toxic catalysts and optimize the reaction conditions to inhibit the occurrence of side reactions and improve the color and stability of PEF products. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing polyethylene 2,5-furandicarboxylate, thereby improving the problem of the dark color of polyethylene 2,5-furandicarboxylate.

[0007] The preparation method of polyethylene 2,5-furandicarboxylate of the present invention comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add activated carbon to water, ultrasonicate, then mix and dissolve 2,5-furandicarboxylic acid, alkali and water, add to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylate; (1-2) heating the solution to 60-80° C., passing the aqueous solution of 2,5-furandicarboxylic acid salt through a chromatography column loaded with LXC-20 dealdehyde resin and a chromatography column loaded with a modified adsorbent for adsorption, respectively, to purify the 2,5-furandicarboxylic acid salt solution, adding acid to adjust the pH to 2-4, so that 2,5-furandicarboxylic acid precipitates, filtering, and drying to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of non-polar macroporous adsorption resin particles, 1-5 parts of methyl anthranilate, 2-8 parts of 2,3,4,5,6-pentahydroxyhexanal, 500-1000 parts of water, 2-5 parts of polyvinyl alcohol, and 1-1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 85-95° C., filtered, and dried to obtain the modified adsorbent.

[0008] (2) Purified 2,5-furandicarboxylic acid, ethylene glycol, a composite catalyst and a composite stabilizer are added to a reaction container, and 2,5-furandicarboxylic acid ethylene glycol ester is prepared through esterification reaction and polycondensation reaction.

[0009] The molar ratio of 2,5-furandicarboxylic acid to ethylene glycol is 1:(1.1-2.8).

[0010] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1: (0.1-0.2): (0.4-0.6).

[0011] The usage of the composite catalyst is 0.05-0.1% of the mass of 2,5-furandicarboxylic acid.

[0012] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1: (0.2-0.4).

[0013] The dosage of the composite stabilizer is 0.1-0.5% of the mass of 2,5-furandicarboxylic acid.

[0014] The reaction temperature of the esterification reaction is 160-190° C., and the reaction time is 0.5-1 h.

[0015] The reaction temperature of the polycondensation reaction is 200-230° C., the reaction time is 1.5-2.5 h, and the pressure is 0.05-0.098 KPa.

[0016] The molar ratio of the base in step (1-1) to 2,5-furandicarboxylic acid is (2-3):1; the mass ratio of activated carbon to 2,5-furandicarboxylic acid is (0.1-0.5):1.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention sequentially uses activated carbon, formaldehyde-removing resin and modified adsorbent to purify 2,5-furandicarboxylic acid, which can effectively reduce the content of acyl furoic acid (FFCA), furoic acid (FCA) and aldehyde impurities, reduce the occurrence of side reactions, and reduce the color of the finished product.

[0018] (2) The present invention uses methyl o-aminobenzoate and 2,3,4,5,6-pentahydroxyhexanal to modify the non-polar macroporous adsorption resin, which greatly enhances its adsorption capacity for aldehyde impurities and improves the purity of 2,5-furandicarboxylic acid.

[0019] (3) The present invention adopts a mixture of aluminum acetylacetonate, triphenyl antimony diacetate, and zinc acetate as a catalyst for polyethylene 2,5-furandicarboxylate. Aluminum acetylacetonate and zinc acetate are non-toxic catalysts. The combination of a small amount of triphenyl antimony diacetate catalyst can efficiently catalyze the reaction and reduce the occurrence of etherification and decarboxylation reactions, thereby effectively improving the color of PEF.

[0020] (4) The present invention uses a compound of two stabilizers with a large difference in molecular weight. The trimethyl phosphate stabilizer is easy to migrate to the surface; while the antioxidant 1425 can provide long-lasting protection inside. The two stabilizers work synergistically during the reaction process, inhibiting the oxidation reaction in the reaction process and improving the problem of PEF color difference. DETAILED DESCRIPTION

[0021] The present invention will be further described below with reference to the embodiments.

[0022] Unless otherwise specified, all raw materials used in the examples are commercially available.

[0023] LXC-20 formaldehyde-free resin was purchased from Xi'an Lanxiao Technology New Materials Co., Ltd.; D3520 non-polar macroporous adsorption resin was purchased from Tianjin Xijinna Environmental Protection Materials Technology Co., Ltd.

[0024] Example 1 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 7.8 parts by weight of activated carbon to 300 parts by weight of water, and ultrasonicate for 0.5 h, then mix and dissolve 78 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature is raised to 60° C. The aqueous solution of 2,5-furandicarboxylic acid sodium salt is sequentially passed through a chromatography column filled with LXC-20 dealdehyde resin and a chromatography column filled with a modified adsorbent for adsorption. The flow rate is controlled at 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution. Hydrochloric acid is added to adjust the pH to 2 to precipitate 2,5-furandicarboxylic acid. The solution is filtered and dried to obtain purified 2,5-furandicarboxylic acid. The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 1 part of methyl anthranilate, 8 parts of 2,3,4,5,6-pentahydroxyhexanal, 500 parts of water, 2 parts of polyvinyl alcohol, and 1 part of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, a composite catalyst and a composite stabilizer into a reaction vessel, raise the temperature to 160° C., react for 1 hour to complete the esterification reaction, raise the temperature to 200° C., and the pressure to 0.05 KPa, react for 2.5 hours to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:1.1.

[0025] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.1:0.4.

[0026] The usage of the composite catalyst is 0.05% of the mass of 2,5-furandicarboxylic acid.

[0027] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.2.

[0028] The dosage of the composite stabilizer is 0.1% of the mass of 2,5-furandicarboxylic acid.

[0029] Example 2 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly adding 26 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicating for 0.5 h, then dissolving 52 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, adding the mixture to the ultrasonicated activated carbon and water, stirring for adsorption, and filtering to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature is raised to 80° C. The aqueous solution of 2,5-furandicarboxylic acid sodium salt is sequentially passed through a chromatography column filled with LXC-20 dealdehyde resin and a chromatography column filled with a modified adsorbent for adsorption, and the flow rate is controlled to be 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid is added to adjust the pH to 3 to precipitate 2,5-furandicarboxylic acid, and the solution is filtered and dried to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 5 parts of methyl anthranilate, 2 parts of 2,3,4,5,6-pentahydroxyhexanal, 1000 parts of water, 5 parts of polyvinyl alcohol, and 1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, a composite catalyst and a composite stabilizer into a reaction vessel, raise the temperature to 190° C., react for 0.5 h to complete the esterification reaction, raise the temperature to 230° C., and the pressure to 0.098 KPa, react for 1.5 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of 2,5-furandicarboxylic acid to ethylene glycol is 1:2.8.

[0030] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.2:0.6.

[0031] The usage of the composite catalyst is 0.1% of the mass of 2,5-furandicarboxylic acid.

[0032] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.4.

[0033] The dosage of the composite stabilizer is 0.5% of the mass of 2,5-furandicarboxylic acid.

[0034] Example 3 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 18 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicate for 0.5 h, then mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature was raised to 70° C. The aqueous solution of 2,5-furandicarboxylic acid sodium salt was sequentially passed through a chromatography column filled with LXC-20 dealdehyde resin and a chromatography column filled with a modified adsorbent for adsorption, and the flow rate was controlled to be 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid was added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid, and the solution was filtered and dried to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 3 parts of methyl anthranilate, 5 parts of 2,3,4,5,6-pentahydroxyhexanal, 800 parts of water, 3 parts of polyvinyl alcohol, and 1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, composite catalyst and composite stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0035] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.15:0.5.

[0036] The usage of the composite catalyst is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0037] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.3.

[0038] The dosage of the composite stabilizer is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0039] Comparative Example 1 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: first, add 18 parts by weight of activated carbon to 300 parts by weight of water, and perform ultrasonic treatment for 0.5 h. Then, mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, and add the mixture to the ultrasonic activated carbon and water for stirring and adsorption. After filtering, an aqueous solution of 2,5-furandicarboxylic acid sodium salt is obtained. Hydrochloric acid is added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid. The mixture is filtered and dried to obtain purified 2,5-furandicarboxylic acid. (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, composite catalyst and composite stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0040] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.15:0.5.

[0041] The usage of the composite catalyst is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0042] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.3.

[0043] The dosage of the composite stabilizer is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0044] Comparative Example 2 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 18 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicate for 0.5 h, then mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature is raised to 70° C., and the aqueous solution of 2,5-furandicarboxylic acid sodium salt is adsorbed on a chromatography column filled with LXC-20 dealdehyde resin, and the flow rate is controlled to be 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid is added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid, and the solution is filtered and dried to obtain purified 2,5-furandicarboxylic acid; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, composite catalyst and composite stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0045] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.15:0.5.

[0046] The usage of the composite catalyst is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0047] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.3.

[0048] The dosage of the composite stabilizer is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0049] Comparative Example 3 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 18 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicate for 0.5 h, then mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature is raised to 70° C., and the aqueous solution of 2,5-furandicarboxylic acid sodium salt is adsorbed through a chromatography column filled with a modified adsorbent, and the flow rate is controlled to be 2 BV / h to purify the 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid is added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid, and the solution is filtered and dried to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 3 parts of methyl anthranilate, 5 parts of 2,3,4,5,6-pentahydroxyhexanal, 800 parts of water, 3 parts of polyvinyl alcohol, and 1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, composite catalyst and composite stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0050] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.15:0.5.

[0051] The usage of the composite catalyst is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0052] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.3.

[0053] The dosage of the composite stabilizer is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0054] Comparative Example 4 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 18 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicate for 0.5 h, then mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature was raised to 70° C. The aqueous solution of 2,5-furandicarboxylic acid sodium salt was sequentially passed through a chromatography column filled with LXC-20 dealdehyde resin and a chromatography column filled with a modified adsorbent for adsorption, and the flow rate was controlled to be 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid was added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid, and the solution was filtered and dried to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 3 parts of methyl anthranilate, 5 parts of 2,3,4,5,6-pentahydroxyhexanal, 800 parts of water, 3 parts of polyvinyl alcohol, and 1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, a catalyst and a composite stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0055] The catalyst is triphenyl antimony diacetate.

[0056] The amount of the catalyst used is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0057] The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1:0.3.

[0058] The dosage of the composite stabilizer is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0059] Comparative Example 5 The preparation method of polyethylene 2,5-furandicarboxylate comprises the following steps: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add 18 parts by weight of activated carbon to 300 parts by weight of water, ultrasonicate for 0.5 h, then mix and dissolve 62 parts by weight of 2,5-furandicarboxylic acid, 10 parts by weight of sodium hydroxide and 300 parts by weight of water, add the mixture to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylic acid sodium salt; (1-2) The temperature was raised to 70° C. The aqueous solution of 2,5-furandicarboxylic acid sodium salt was sequentially passed through a chromatography column filled with LXC-20 dealdehyde resin and a chromatography column filled with a modified adsorbent for adsorption, and the flow rate was controlled to be 2 BV / h to purify 2,5-furandicarboxylic acid sodium salt solution, and hydrochloric acid was added to adjust the pH to 4 to precipitate 2,5-furandicarboxylic acid, and the solution was filtered and dried to obtain purified 2,5-furandicarboxylic acid; The preparation method of the modified adsorbent is as follows: by weight, 100 parts of D3520 non-polar macroporous adsorption resin particles, 3 parts of methyl anthranilate, 5 parts of 2,3,4,5,6-pentahydroxyhexanal, 800 parts of water, 3 parts of polyvinyl alcohol, and 1.5 parts of benzoyl peroxide are added into a reaction container, reacted at 90±5° C. for 10 hours, filtered, and dried to obtain the modified adsorbent; (2) Add purified 2,5-furandicarboxylic acid, ethylene glycol, composite catalyst and stabilizer into a reaction vessel, raise the temperature to 180°C, react for 0.5 h to complete the esterification reaction, raise the temperature to 210°C, and the pressure to 0.08 KPa, react for 2 h to complete the polycondensation reaction, and obtain ethylene glycol 2,5-furandicarboxylate; The molar ratio of the 2,5-furandicarboxylic acid to ethylene glycol is 1:2.

[0060] The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1:0.15:0.5.

[0061] The usage of the composite catalyst is 0.07% of the mass of 2,5-furandicarboxylic acid.

[0062] The stabilizer is trimethyl phosphate.

[0063] The amount of the stabilizer used is 0.3% of the mass of 2,5-furandicarboxylic acid.

[0064] The mass percentage of the purified 2,5-furandicarboxylic acid in Examples 1-3 and Comparative Examples 1-5 was detected by gas chromatography; Ethylene 2,5-furandicarboxylate prepared in Examples 1-3 and Comparative Examples 1-5: The intrinsic viscosity is tested using the GB / T14190-2017 method; the chromaticity is the Lab value, measured using a Hunter LabColorFlex EZ colorimeter according to the GB / T14190-2017 method, L: color brightness, chromaticity: a, b, where a represents the red-green axis, and b represents the yellow-blue axis.

[0065] The test results are shown in Table 1: Table 1 Test results

[0066] In summary, the embodiment uses activated carbon, formaldehyde-removing resin and modified adsorbent to purify 2,5-furandicarboxylic acid in turn, which can effectively reduce the content of acyl furoic acid (FFCA), furoic acid (FCA) and aldehyde impurities, reduce the occurrence of side reactions, and reduce the color of the finished product. Methyl anthranilate and 2,3,4,5,6-pentahydroxyhexanal modify the non-polar macroporous adsorption resin to further improve the purity of 2,5-furandicarboxylic acid. A mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate is used as a catalyst for polyethylene 2,5-furandicarboxylate, which is more conducive to effectively improving the color of PEF. The compound use of the two stabilizers is more conducive to improving the problem of poor color of PEF.

Claims

1. A method for preparing polyethylene 2,5-furandicarboxylate, characterized in that: The following steps are involved: (1) Purification of 2,5-furandicarboxylic acid: (1-1) firstly add activated carbon to water, ultrasonicate, then mix and dissolve 2,5-furandicarboxylic acid, alkali and water, add to the ultrasonicated activated carbon and water, stir and adsorb, and filter to obtain an aqueous solution of 2,5-furandicarboxylate; (1-2) raising the temperature, passing the aqueous solution of 2,5-furandicarboxylic acid salt through a chromatography column loaded with a de-aldehyde resin and a chromatography column loaded with a modified adsorbent for adsorption, respectively, to purify a 2,5-furandicarboxylic acid salt solution, adding acid to adjust the pH to precipitate 2,5-furandicarboxylic acid, filtering, and drying to obtain purified 2,5-furandicarboxylic acid; (2) adding purified 2,5-furandicarboxylic acid, ethylene glycol, a composite catalyst and a composite stabilizer into a reaction container, and performing esterification reaction and polycondensation reaction to obtain ethylene glycol 2,5-furandicarboxylate; The modified adsorbent is prepared by modifying a non-polar macroporous adsorption resin with methyl anthranilate and 2,3,4,5,6-pentahydroxyhexanal; The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate; The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425; The molar ratio of 2,5-furandicarboxylic acid to ethylene glycol is 1:(1.1-2.8).

2. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The preparation method of the modified adsorbent comprises the following steps: adding non-polar macroporous adsorption resin particles, methyl anthranilate, 2,3,4,5,6-pentahydroxyhexanal, water, polyvinyl alcohol and benzoyl peroxide into a reaction container, heating the reaction, filtering and drying to obtain the modified adsorbent.

3. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The composite catalyst is a mixture of aluminum acetylacetonate, triphenyl antimony diacetate and zinc acetate in a molar ratio of 1: (0.1-0.2): (0.4-0.6).

4. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The usage of the composite catalyst is 0.05-0.1% of the mass of 2,5-furandicarboxylic acid.

5. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The composite stabilizer is a mixture of trimethyl phosphate and antioxidant 1425 in a mass ratio of 1: (0.2-0.4).

6. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The dosage of the composite stabilizer is 0.1-0.5% of the mass of 2,5-furandicarboxylic acid.

7. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The reaction temperature of the esterification reaction is 160-190° C., and the reaction time is 0.5-1 h.

8. The method for preparing polyethylene 2,5-furandicarboxylate according to claim 1, characterized in that: The reaction temperature of the polycondensation reaction is 200-230° C., the reaction time is 1.5-2.5 h, and the pressure is 0.05-0.098 KPa.

Citation Information

Patent Citations

  • Method for purifying furandicarboxylic acid

    CN103965146A

  • Method for purifying biobased 2,5-furandicarboxylicacid

    CN105732551A

  • Polyester for heat shrinkable film and preparation method thereof

    CN112679709A

  • Preparation method of low-chroma PETG copolyester

    CN114891189A

  • Preparation method of poly (ethylene 2, 5-furandicarboxylate)

    CN117209740A

Cited By

  • Method for preparing high-molecular-weight polyethylene furandicarboxylate by one-step method

    CN121699122A